2004
DOI: 10.1002/pssb.200404958
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic electron–phonon effects in low carrier density superconductors

Abstract: Different families of unconventional superconductors present a low charge carrier density as a common trait, suggesting that the low charge density can be at the basis of a unifying picture for different superconductors. In the past years we have suggested that the electron -phonon interaction can be responsible for a high-c T superconducting pairing in a nonadiabatic regime, where nonadiabatic effects are triggered on by the small electronic Fermi energy associated with the low charge density character. A coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…el−ph ≃ 1.7 − 1.9. Moreover, it was pointed out by Cappelluti et al [2] that nonadiabatic character can be further enhanced by low charge carrier density, that is the case for ZrB 12 [4,5].…”
mentioning
confidence: 98%
“…el−ph ≃ 1.7 − 1.9. Moreover, it was pointed out by Cappelluti et al [2] that nonadiabatic character can be further enhanced by low charge carrier density, that is the case for ZrB 12 [4,5].…”
mentioning
confidence: 98%
“…We performed calculations of the phonon spectral functions at different temperatures (Eqs. [2][3][4][5] for both excitation wavelengths. The results obtained (Fig.…”
Section: B Group IV Metals -Zirconium and Titaniummentioning
confidence: 99%
“…This may increase the superconducting transition temperature T c in correlated electron systems 3 . In the past years it has been proposed [4][5][6] that nonadiabatic effects in electron-phonon interaction could be responsible for the high-temperature superconductivity in compounds with low carrier density such as fullerenes 7 or MgB 2 8 . The recent measurement of Raman spectra in graphite intercalation compounds 9,10 showed that the phonon frequencies related to in-plane carbon vibrations are significantly larger than those obtained from density functional theory (DFT) calculations in the adiabatic approximation.…”
Section: Introductionmentioning
confidence: 99%
“…In regards with the nonadiabatic features, fullerides represent a very important test since, due to the extremely high frequencies of the intra-molecular phonon spectrum and to the weak inter-molecular electron hopping [74][75][76], the nonadiabatic ratio w ph /E F is significantly large, w ph /E F 0.4-0.8 [74,75]. On the other hand, in cuprates the two-dimensional character of the electronic band and the closeness of the Fermi level to a logarithmic Van Hove singularity [77] permit to investigate additional nonadiabatic effects triggered by the flatness of the electronic bands near the Van Hove saddle point.…”
Section: Nonadiabatic Superconductivity In Fullerides and Cupratesmentioning
confidence: 99%